2017
DOI: 10.4172/pharmaceutical-sciences.1000292
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cognitive Impairment in Type 2 Diabetic Rats

Abstract: Among all the secondary complications of type 2 diabetes, cognitive impairment associated with diabetes is less well studied and characterized. We made an attempt to investigate the molecular mechanisms involved in cognitive decline in high fat diet-streptozotocin model of type 2 diabetes. High-fat diet and a single low dose streptozotocin (25 mg/kg) were used to induce diabetes in Sprague-Dawley rats. Developments of cognitive deficit in these animals were measured using change in transfer latency in elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
2
7
0
1
Order By: Relevance
“…Bicyclol, a novel type synthetic antihepatitic drug can control the elevation of aminotransferase induced by chronic hepatitis. For other liver diseases such as cirrhosis, liver fibrosis, drug-induced hepatitis, Bicyclol reduced the liver function impairment induced by antithyroid drugs, which is in line with studies reported [10][11][12][13][14][15] .…”
Section: As Shown In Tablesupporting
confidence: 87%
“…Bicyclol, a novel type synthetic antihepatitic drug can control the elevation of aminotransferase induced by chronic hepatitis. For other liver diseases such as cirrhosis, liver fibrosis, drug-induced hepatitis, Bicyclol reduced the liver function impairment induced by antithyroid drugs, which is in line with studies reported [10][11][12][13][14][15] .…”
Section: As Shown In Tablesupporting
confidence: 87%
“…Application of RTSWE can prevent 50-60 % of patients from undergoing liver puncture. This study proved that the research group had better liver stiffness, liver function indexes and liver fibrosis indexes than the control group, which is consistent with the relevant findings [9][10][11][12][13][14][15] (Tables 1 and 2). RTSWE could accurately determine the degree of liver fibrosis.…”
supporting
confidence: 89%
“…[ 32 ] Minocycline may also reduce hippocampal astrogliosis in vascular dementia model in rats, while our previous work also showed astrogliosis and microglial activation in diabetic rat brain. [ 14 33 ] We also saw a reduction in hippocampal chemokine, monocyte chemoattractant protein-1 levels by minocycline suggesting reduced astrogliosis in MetS brain (preliminary observation in our laboratory). While microglia-associated inflammation, leading to amyloidopathy and tauopathy, which has been reported in diabetic animal brain, minocycline, principally, acts on microglial cells [ 34 ] and may alleviate this Alzheimer's disease-like pathology through inhibition of nuclear factor-kappaB.…”
Section: Discussionmentioning
confidence: 63%